Comparison of Symmetric and Asymmetric Copper Tubing Designs for Improved Cooling in PV/T Systems - Riad Ayoub; Amiry Houssam; Touhtouh Samira; Belhora Fouad; Hajjaji Abdelowahed (E3S Web of Conferences)
This paper presents an enhanced cooling approach for Photovoltaic/Thermal (PV/T) systems aimed at improving the thermal management and overall efficiency of photovoltaic cells. The comparative study investigates two novel copper tubing designs: symmetric and asymmetric serpentine configurations. Both designs were tested under identical conditions with a water flow rate of 2.44 L/min to analyze their influence in reducing the operating temperature of the PV modules. The numerical results show that the symmetric design reduced the PV module temperature from 50°C to 39.8°C, resulting in an electrical efficiency of 16.80% and a thermal efficiency of 20.3%. In contrast, the asymmetric design lowered the temperature to 42.7°C, achieving an electrical efficiency of 16.57% and a thermal efficiency of 30.40%. The findings demonstrate that while the symmetric system excels in electrical efficiency, the asymmetric design offers enhanced thermal energy recovery. Overall, the symmetric system achieved an overall efficiency of 20.81%, while the asymmetric design reached 29.40%. The results of this study provide valuable insights into the design of efficient cooling systems for PV/T modules, helping to strike a balance between electrical and thermal performance in real-world applications.